2021
DOI: 10.3390/jpm11090883
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABCA1 Gene Polymorphisms and Plasma Lipid Concentration: A Systematic Review and Meta-Analysis

Abstract: Background: Although ABCA1 gene polymorphisms may be associated with the plasma lipid concentration, the literature has not shown a consistent pattern. In this study, we attempted to elucidate the association between the ABCA1 69C>T, 825V>I, and 230R>C polymorphisms and the plasma lipid concentration through a systematic review and meta-analysis. Methods: We selected studies published up to October 2020 in the PubMed, Web of Science, and Embase databases according to inclusion and exclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous studies suggested that the ABCA1 C69T polymorphism variant is the upstream variant of ABCA1 gene (ENST00000374736.8) in the non-coding region shown to be associated with a decreased incident rate of T2DM [ 26 ]. In addition, a recent meta-analysis of studies conducted on Asian people (mainly Chinese) reached the same conclusion [ 20 ]. However, ethnicity has been reported to play a role in the determination of genetic risk factors [ 27 , 28 ], and indeed, others have reported no effects in Bangladeshi [ 29 ], Malaysian [ 30 ], or Caucasian subjects [ 31 ].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies suggested that the ABCA1 C69T polymorphism variant is the upstream variant of ABCA1 gene (ENST00000374736.8) in the non-coding region shown to be associated with a decreased incident rate of T2DM [ 26 ]. In addition, a recent meta-analysis of studies conducted on Asian people (mainly Chinese) reached the same conclusion [ 20 ]. However, ethnicity has been reported to play a role in the determination of genetic risk factors [ 27 , 28 ], and indeed, others have reported no effects in Bangladeshi [ 29 ], Malaysian [ 30 ], or Caucasian subjects [ 31 ].…”
Section: Introductionmentioning
confidence: 66%
“…However, in most cases, prediabetes remains undiagnosed and hence untreated, allowing further deterioration in metabolic regulation and worsening micro and macro-vascular complications [ 7 , 8 , 9 ]. Indeed, studies have shown an association between prediabetes and increased risk of complications of diabetes such as early nephropathy, small fiber neuropathy, early retinopathy and risk of macrovascular disease [ 17 , 18 , 19 , 20 , 21 ]. In contrast, an Iranian study reported an association between dyslipidemia and prediabetes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences were observed between the case and control groups, depicting that there is a possibility of an inherent disruption in HDL-c metabolism among the Indian population. A previous meta-analysis conducted by Shim et al (11), reported on the inconsistencies in lipid levels and ABCA1 variants. The association between the two SNPs and lipid profiles was assessed in the present study, and no substantial association (P>0.05) was found for these parameters and the genotype distribution (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the genetic polymorphism in the ABCA1 gene and the decrease in HDL-c levels has been demonstrated in recent years (10). A systematic review and meta-analysis on studies that determined the association between the ABCA1 gene polymorphism and T2DM, revealed inconsistent results (11). The divergence may be due to the influence of ethnicity, genetic susceptibility, and environmental factors.…”
Section: Discussionmentioning
confidence: 99%